2020
DOI: 10.32934/jmie.v4i1.170
|View full text |Cite
|
Sign up to set email alerts
|

Project-Based Learning - Literacy in Improving Students’ Mathematical Reasoning Abilities in Elementary Schools

Abstract: The lower mathematical reasoning abilities of elementary school students are the background of this research. This happens because students have not been properly facilitated to develop the ability mathematical of reasoning. Mathematics learning can develop reasoning ability well because mathematics learning has systematic concepts and conceptual relationships. This will have an impact on logical, systematic and rational ways of thinking. Therefore, teachers must be able to choose learning models that can faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 4 publications
1
7
0
7
Order By: Relevance
“…This is consistent with the findings of several studies, which demonstrate that projectbased learning strategies can assist students with low learning autonomy in determining good learning paths to achieve learning goals and allow students to investigate things in depth with direct teacher guidance (Mahasneh & Alwan, 2018). When taught to kids with low learning autonomy, project-based learning strategies can boost creativity and student learning outcomes (Abidin et al, 2020;Jalinus et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the findings of several studies, which demonstrate that projectbased learning strategies can assist students with low learning autonomy in determining good learning paths to achieve learning goals and allow students to investigate things in depth with direct teacher guidance (Mahasneh & Alwan, 2018). When taught to kids with low learning autonomy, project-based learning strategies can boost creativity and student learning outcomes (Abidin et al, 2020;Jalinus et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Keberadaan pembelajaran matematika di sekolah perlu disadari kepentingannya, matematika wajib untuk siswa dari tingkat dasar dan menengah. Pada era pengembangan ilmu pengetahuan dan teknologi, manfaat dan kegunaan pelajaran matematika bagi anak merupakan hal yang penting dan tidak perlu dipertimbangkan (Abidin et al, 2020).…”
Section: Pendahuluanunclassified
“…Several studies have found that math literacy (including in the learning process) of primary school students is still in the "medium" and "low" groups (Ekawati et al, 2020;Fadillah & Ni'mah, 2019). Meanwhile, another study states that students' math literacy performance can be improved through learning that is integrated with literacy activities and familiarizing students with math literacy-based problems to facilitate students in improving their mathematical reasoning abilities (Abidin et al, 2020;Zainiyah & Marsigit, 2019). Thus the development of studies related to math literacy shows that the main factor that causes low primary students' math literacy is due to the unavailability of math literacy-based problems in learning activities at primary school.…”
Section: Introductionmentioning
confidence: 99%